Comparison of Taiji and aerobic exercise for functional constipation: study protocol for a randomised controlled neuroimaging trial - Tianyu Liu; Sha Yang; Jingwen Chen; Yuyi Guo; Yuke Teng; Rongtao Ying; Zhaoxuan He; Jianwei Wu; Shu-Guang Yu; Fang Zeng (BMJ Open)
Introduction Taiji has been proven to be effective for regulating both the physical and mental state compared with simple aerobic exercise. However, whether the improvement of Taiji for constipation is related to regulate imbalanced brain–gut axis and emotional disorder for functional constipation (FC) remains uncertain. The results of the study will demonstrate the differences in regulation brain–gut balance between Taiji and simply aerobic exercise for patients with FC and provide a potential therapy for clinical treatment of FC, and a new approach for the research of mind–body exercise.Methods and analysis In this randomised controlled neuroimaging trial, 80 patients with FC will be allocated into two groups: Taiji group and aerobic exercise group. The two groups will receive 10 weeks of Taiji exercise or aerobic exercise, respectively. The stool diary, Cleveland Constipation Score and Patient Assessment of Constipation Symptom, Patient Assessment of Constipation Quality of Life Questionnaire will be used to evaluate the clinical efficacy, the Self-rating Depression Scale, Self-rating Anxiety Scale, Eysenck Personality Questionnaires and Mini-Mental State Examinations will be used to assess the mental state at the baseline, the 5-week intervention and the end of intervention. The 24-hour heart rate variability will be used for assessing the autonomic nervous function, functional MRI and positron emission tomography-CT will be performed for detecting the cerebral functional changes at the baseline and the end of the intervention. The clinical data and multimodal imaging data will be analysed, respectively. Correlation analysis will be conducted to investigate the relationship between cerebral functional changes and symptom improvement.Ethics and dissemination The procedures have been approved by the Sichuan Regional Ethics Review Committee on Traditional Chinese Medicine (No. 2018KL-047) and conformed to the Declaration of Helsinki. Results will be disseminated through policy briefs, workshops, peer-reviewed publications and conferences.Trial registration number Chinese Clinical Trial Registry (ChiCTR1800019781).